El uso excesivo de las redes sociales y su influencia en el rendimiento académico en estudiantes de noveno año de educación básica - Pereira Salguero, Jennifer Estefania (2025)
The purpose of this research work was to analyze the relationship between digital interaction and school performance, considering the growing presence of these platforms in the daily lives of adolescents. The study was developed under a quantitative approach, with correlational scope, using a non-experimental-cross-sectional design, applied to a population of 68 students from the Juan Montalvo Educational Unit. For the variable use of social networks, a structured questionnaire was applied that allowed identifying the level of frequency and intensity of interaction, while academic performance was determined from the average grades in Language and Literature, Mathematics, Natural Sciences and Social Studies, interpreted through the official rating scale of the Ministry of Education. The statistical analysis included the elaboration of descriptive tables, histograms of frequency distribution and Spearman's correlation to establish the degree of relationship between the variables. The results showed that students mostly present a moderate use of social networks and an academic performance located in medium-high ranges, with the presence of individual differences in specific areas. Likewise, a positive association of high magnitude was identified between both variables, which suggests that, within the group studied, a greater use of social networks is related to better academic scores, although without implying direct causality. The study concludes that digital use, when regulated, oriented and pedagogically used, can coexist with favorable academic performance providing relevant evidence to strengthen responsible digital education and institutional planning aimed at meaningful learning.